Imaging: Upconversion Nanoparticles as a Contrast Agent for Photoacoustic Imaging in Live Mice (Adv. Mater. 32/2014). (August 2014) - Maji, Swarup Kumar; Sreejith, Sivaramapanicker; Joseph, James; Lin, Manjing; He, Tingchao; Tong, Yan; Sun, Handong; Yu, Sidney Wing‐Kwong; Zhao, Yanli
<x xml:space="preserve">Abstract</x> Photoacoustic imaging has evolved as a promising deep‐tissue optical imaging modality. On page 5633, Y. Zhao and co‐workers demonstrate the inclusion complex of NaYF4:Yb3+, Er3+ upconversion nanoparticles with α‐cyclodextrin in aqueous conditions that exhibits luminescence quenching when excited at 980 nm. This non‐radiative relaxation leads to photoacoustic signal enhancement in vivo, showing high capability of the material for photoacoustic imaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>